Transactional engineering for green airports maximizing taxiing energy recovering case - Tifrit, Abdelkrim; Benabdallah, Tawfik; Benchenane, Halima (International Journal of Innovative Research and Scientific Studies, 2025)
This work explores the KERPS system (Kinetic Energy Recovery by Pressure on Slabs) as a solution for harnessing kinetic energy from aircraft taxiing. By embedding piezoelectric slabs in airport runways and taxiways, the system aims to convert aircraft-induced mechanical vibrations into electrical energy, enhancing airport sustainability and reducing reliance on conventional power sources, in line with COP recommendations on energy transition and carbon footprint reduction. Using MATLAB and COMSOL Multiphysics, this study analyzes the interaction between a Boeing 747’s landing gear and the piezoelectric slabs, considering key parameters such as mass, velocity, damping, and resonant frequency. Simulations indicate that an empty Boeing 747 can generate up to 55 kW, while a fully loaded aircraft produces approximately 53 kW. To optimize energy use, a lithium battery storage system is proposed for energy retention and redistribution. By aligning the resonance frequency of the slabs with aircraft-induced vibrations, the system improves energy conversion efficiency, making self-sufficient airports a viable reality. This study supports the adoption of KERPS technology to power airport infrastructure while meeting the requirements of engineering firms and energy auditors seeking sustainable, high-performance solutions, fully aligned with global commitments to sustainability and carbon neutrality.